Associations between environmental perchlorate, nitrate, and thiocyanate exposure and severe headache or migraine: a cross-sectional, population-based analysis - Mao, Jiesheng; Zhou, Mi; Yanjun, Li; Zhao, Yunhan; Hu, Haoxiang; Yang, Xiaokai (Frontiers in Neurology, 2024)
Background Environmental contaminants may play a significant role in the development of migraine. Perchlorate, nitrate, and thiocyanate were selected for this study due to their known impact on thyroid function, which is closely linked to neurological processes. Disruptions in thyroid function have been associated with various neurological disorders, including migraines. However, there is currently no evidence linking exposure to these specific chemicals to migraine. The study aims to evaluate the association between urinary concentrations of perchlorate, nitrate, and thiocyanate with the prevalence of severe headache or migraine in U.S. adults. Methods A cross-sectional study was conducted using data from the National Health and Nutrition Examination Survey (NHANES) 2001–2004. Utilizing electrospray tandem mass spectrometry in conjunction with ion chromatography, urinary concentrations of perchlorate, nitrate, and thiocyanate urine were measured. Multiple logistic regression models were employed to evaluate the linear correlation between perchlorate, nitrate, and thiocyanate exposure and severe headache or migraine. The non-linear relationship is described analytically using a fitted smoothing curve and a two-piecewise regression model. Subgroup analyses were used to further clarify the stability of this relationship across different populations. Results There were 1,446 participants in this population-based study, ranging in age from 20 to 85. After adjusting for potential confounding variables, the multiple logistic regression findings demonstrated that thiocyanate was significantly positively associated with the prevalence of migraine (odds ratio [OR] = 1.18; [1.06, 1.30]; p < 0.001). There was consistency in this connection across different subgroups (p for interaction >0.05). Furthermore, there was a non-linear correlation between urinary thiocyanate and migraine. Using a fitted smoothing curve and a two-piecewise regression model, it was found that the correlation between urinary thiocyanate and migraine was U-shaped (p for Log-likelihood ratio = 0.002). According to the findings of the multiple regression analysis, there was no significant correlation between urinary perchlorate and nitrate and migraine (both p > 0.05). Conclusion We should limit our exposure to thiocyanate by keeping it within a reasonable range, as indicated by the U-shaped correlation between urinary thiocyanate and migraine.